Weather-based models to forecast spot blotch disease (Bipolaris sorokiniana) of wheat (Triticum aestivum) in North Bengal - CHATTOPADHAY, NIVEDITA; KUMAR, AMRENDER; MANDAL, RUPSANATAN; ROY, AYON; BHATTACHARYA, PRATEEK MADHAB; CHOWDHURY, APURBA KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Experiment was laid with wheat (Triticum aestivum L.) genotypes Sonalika (susceptible check) and HD 2967 (popular variety) at Pundibari, Coochbehar, India (26o23’52”N, 89o23’26”E) on two dates of post-rainy (rabi) seasons of 2018 and 2019 at one-year interval. Data of experiments conducted previously at Pundibari were also used. Correlation values indicated that percent disease severity and Area under Disease Progress Curve on cv. Sonalika and HD 2967 had significant (P<0.1) correlations with maximum temperature and morning relative humidity. Weighted interactions between maximum temperature and morning relative humidity, maximum temperature and rainfall, minimum temperature and afternoon relative humidity, minimum temperature and rainfall, morning and afternoon relative humidity were also significant (P<0.1). Cultivar-specific models were developed to predict the severity of the spot blotch disease (Bipolaris sorokiniana) on the crop. This will allow the growers to make need-based timely effective application of fungicides prior to inception of the disease. Here we report only the models that were found effective based on validation in the two years. As per available literature, this report seems to be the first of its kind for forecasting spot blotch of wheat.